Measurement and analysis of agricultural Productivity in colombia (2018)
Tremendous agricultural potential in Colombia has gone untapped for decades due to: i) civil strife and the criminal drug trade; ii) uncertain property rights; iii) inadequate infrastructure; iv) lack of innovation and technological development; v) lack of funding, vi) lack of investment; and vii) misallocation of resources within the sector. Proof of this is the relatively lower growth of the value of Colombia’s agriculture versus other countries in the region during the agricultural prices booms (FAO, 2015). This paper analyzes whether Colombia’s weak agricultural performance was due to low productivity growth rather than input accumulation. Using econometric specifications, this paper finds that Colombia’s agricultural productivity grew on average between 0.8% and 1.3% annually from 1975 and 2013. This growth was mainly driven by livestock and poultry productivity, which grew between 1.6% and 2.2%, while crop productivity grew between 0% and 0.8%. Likewise, this paper finds biased technical and scale effects whenever the models are able to test their presence. In addition, it finds evidence that Colombia’s agricultural productivity growth was affected by changing economic circumstances. These results are significant for post-conflict rural investment because they provide information about the returns on future government investment options in the rural sector of Colombia.